An expanded population of pathogenic regulatory T-cells in giant cell arteritis is abrogated by IL-6 blockade therapy - Miyabe, Chie (Ann Rheum Dis, 2016)
OBJECTIVES: Randomized-controlled trials have recently proven the efficacy of the interleukin-6 receptor antagonist tocilizumab (TCZ) in GCA. However, the mechanism of action of IL-6 blockade in this disease is unknown. Moreover, the role of regulatory T-cells (Treg) in the pathogenesis of GCA remains underexplored. Given the plasticity of Tregs and the importance of IL-6 in their biology, we hypothesized that TCZ might modulate the Treg response in GCA. We therefore characterized the Treg compartment of GCA patients treated with TCZ METHODS: We classified 41 GCA patients into 3 groups: active disease (aGCA, n=11); disease remission on corticosteroids (rGCA-CS, n=19); and disease remission on TCZ (rGCA-TCZ, n=11). Healthy controls were included for comparison. We determined the frequency, phenotype and function of peripheral blood Tregs. RESULTS: aGCA patients demonstrated a hypoproliferating Treg compartment enriched in IL-17-secreting Tregs (IL-17(+)Tregs). Tregs in aGCA patients disproportionally expressed a hypofunctional isoform of Foxp3 that lacks exon 2 (Foxp3Δ2). Foxp3Δ2-expressing Tregs co-expressed CD161, a marker commonly associated with the Th17 linage, significantly more often than full-length Foxp3-expressing Tregs. Compared to those of healthy controls, GCA-derived Tregs demonstrated impaired suppressor capacity. Treatment with TCZ, in contrast to CS therapy, corrected the Treg abnormalities observed in aGCA. In addition, TCZ treatment increased the numbers of activated Tregs (CD45RA(−)Foxp3(high)) and the Treg expression of markers of trafficking (CCR4) and terminal differentiation (CTLA-4). CONCLUSIONS: TCZ may exert its therapeutic effects in GCA by increasing the proliferation and activation of Tregs, and by reverting the pathogenic Treg phenotype seen during active disease.